Sistem Pakar Mendiagnosa Penyakit Pada Tanaman Cabe Berbasis Web - Gultom, Heman Hottua; Yenni, Yusli (LPPM Universitas Putera Batam, 2021)
Technological advances apply a system to solve a problem that takes the knowledge of an expert. This knowledge covers many fields of science, for example, the field of agriculture can apply an expert system to the analysis of chili plant diseases. The problem of recognizing the symptoms of chili plant diseases has resulted in farmers failing to harvest. An expert system is a collection of knowledge from an expert poured in machine language. In the expert system, the characteristics of the disease are converted into code and then translated by the computer. Forward Chaining is a technique that becomes a reference for conducting searches with forward tracking systems referring to conclusions. The development of an expert system involves several supporting software, UML as a workflow for the system. Notepad ++ is text editor processing HTML and PHP programming languages ​​with a CSS complement to process HTML elements. XAMPP serves as a liaison to access databases in MySQL. Web-based applications are designed to be accessed farmers by internet. The application can recognize the symptoms of the disease and determine the solution to the problem. Farmers are expected to use the application of information to avoid crop failure due to chili disease.